1953
DOI: 10.1172/jci102803
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the Effects of Magnesium Sulfate on Renal Function, Electrolyte Excretion, and Clearance of Magnesium 1

Abstract: The effect of the parenteral administration of magnesium sulfate on the renal hemodynamics of normal dogs (1) and normal children (2) has been previously reported. However, no data are available concerning the effects of magnesium sulfate on the excretion of other electrolytes, nor have studies on the renal clearance of magnesium been reported. It is the purpose of this report to present such data. METHODSStudies of renal function, electrolyte excretion, and the clearance of magnesium were performed on six you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1958
1958
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…Although several investigators (1)(2)(3)(4)(5)(6)(7)(8) have shown that the renal clearance (or excretion) of magnesium increases after the injection of magnesium salts, no data have been published to show how the renal clearance of magnesium depends upon the serum magnesium concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several investigators (1)(2)(3)(4)(5)(6)(7)(8) have shown that the renal clearance (or excretion) of magnesium increases after the injection of magnesium salts, no data have been published to show how the renal clearance of magnesium depends upon the serum magnesium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators (3)(4)(5)(6) have since found that the magnesium clearance increases after the injection of magnesium salts, although what appears to be the only study systematically relating clearances to plasma concentrations of magnesium has been published only in abstract form (7,8).…”
mentioning
confidence: 99%
“…Potassium excretion in man usually decreases following parenteral injection of magnesium salts (32,33) (Table II). The hypothesis has been suggested that magnesium, a divalent ion, may enter into a univalent ion exchange mechanism, resulting in a decreased excretion of potassium (32).…”
Section: Effect Of Acid-base Changesmentioning
confidence: 99%
“…The hypothesis has been suggested that magnesium, a divalent ion, may enter into a univalent ion exchange mechanism, resulting in a decreased excretion of potassium (32). The failure of potassium chloride ingestion to produce a consistent effect on magnesium excretion does not lend support to such a suggestion (34).…”
Section: Effect Of Acid-base Changesmentioning
confidence: 99%
“…Moreover, magnesium infusion decreases urinary K ϩ excretion in normal individuals. 7 K ϩ is freely filtered at the glomerulus. Most of the filtered K ϩ is reabsorbed by the proximal tubule and the loop of Henle.…”
mentioning
confidence: 99%